Development and psychometrics measurement scales of factors affecting the establishment of teledermatology - Beigom Kazemi, Sakineh; Jafari, Mehrnoosh; Hosseini, Seyed Mojtaba; Maher, Ali; Bahadori, Mohammad Karim (Researcher Bulletin of Medical Sciences, 2022)
Purpose: Despite its vast benefits, the establishment of telemedicine, especially teledermatology, faces many problems due to several reasons. The present study was carried out with the purpose of psychometrics measurement of the factors affecting the establishment of teledermatology. Materials and Methods: The present mixed-method (qualitative and quantitative) study was carried out through triangulation in 2018. The research population comprises experts and managers of the health system of Iran. Cronbach's alpha test was used to assess the internal consistency, and the external reliability was measured by the test-retest method. The significance level throughout the whole analysis was P<0.05. Results: According to the scree plot, the eigenvalues were greater than 1 and the slope of the scree plot, 8 factors with the potential of predicting the 69.52% of the total changes of the factors of the establishment of the telemedicine were extracted and selected. Cronbach's alpha test was employed to determine the internal consistency of the questionnaire, which was approved with the amount of 0.941 (higher than 0.7). Conclusion: The results indicated that the 58-article measurement scale for the factors influencing the establishment of teledermatology has good validity and reliability. According to factor analysis, it includes 8 subscales. Cronbach's alpha coefficient was calculated to be equal to 0.941.